Persepsi Masyarakat Terhadap Kualitas Madu Apis Mellifera Jambi Dengan Menggunakan Metode Analisis Importance Performance - LESTARI, WENI; Rodhiyah, Rodhiyah (Jurnal Khazanah Intelektual, 2024)
The fact that Apis mellifera honey exists and can be used as a superior regional product has made the people of Jambi proud. The better the quality of honey, the more satisfied the community will be. Thus, every effort that leads to improving the quality of honey needs to be encouraged. Behavior of individuals who consume honey influences perception. This study aims to determine the public’s perception of cultivated honey. This research uses the importance performance method in qualitative descriptive setting. In general, the public’s perception of the quality of Apis mellifera honey is in accordance with their level of expectations. The solutions offered is to include informations on the honey packaging in the form of a halal label and expiration date, educate the public that Apis mellifera honey does have a distinctive smell, expand the market so that people can obtain the product easlily, make flavor varients, attractive packaging, and intensive promotion. Keywords: Honey, Perception, Quality